PPARγ Ligands Regulate Noncontractile and Contractile Functions of Airway Smooth Muscle: Implications for Asthma Therapy - Chantal Donovan; Xiahui Tan; Jane Elizabeth Bourke (PPAR Research)
In asthma, the increase in airway smooth muscle (ASM) can contribute to inflammation, airway wall remodeling and airway hyperresponsiveness (AHR). Targetting peroxisome proliferator-activated receptor γ (PPARγ), a receptor upregulated in ASM in asthmatic airways, may provide a novel approach to regulate these contributions. This review summarises experimental evidence that PPARγ ligands, such as rosiglitazone (RGZ) and pioglitazone (PGZ), inhibit proliferation and inflammatory cytokine production from ASM in vitro. In addition, inhaled administration of these ligands reduces inflammatory cell infiltration and airway remodelling in mouse models of allergen-induced airways disease. PPARγ ligands can also regulate ASM contractility, with acute treatment eliciting relaxation of mouse trachea in vitro through a PPARγ-independent mechanism. Chronic treatment can protect against the loss of bronchodilator sensitivity to β2-adrenoceptor agonists and inhibit the development of AHR associated with exposure to nicotine in utero or following allergen challenge. Of particular interest, a small clinical trial has shown that oral RGZ treatment improves lung function in smokers with asthma, a group that is generally unresponsive to conventional steroid treatment. These combined findings support further investigation of the potential for PPARγ agonists to target the noncontractile and contractile functions of ASM to improve outcomes for patients with poorly controlled asthma.